Effects of moderate-intensity continuous training therapy on claudication symptoms and carotid intima-media thickness in patients after endovascular and classical bypass treatment (a pilot study) - Sid Solaković; Anes Jogončić; Ratko Pavlović; Mensur Vrcić; Nedim Čović; Emir Solaković; I. T. Skrypchenko; Denis Čaušević; O. Ye. Dorofieieva; K. S. Yarymbash (Zaporožskij Medicinskij Žurnal)
Research on moderate-intensity continuous training (MICT) is closely connected with primary and secondary cardiovascular protection but also can be associated with primary bypass patency and outcome of endovascular treatment for critical iliac stenosis TASC II A and B. After specific surgical or non-surgical treatment, iliac bypass or endovascular revascularization patency still depends on an individual and is still in the eye of scientific research modalities. Carotid intima-media thickness (CIMT) is an efficient surrogate parameter in detection and prediction of cerebrovascular events and potential marker of generalized atherosclerosis with prognosis of peripheral arterial disease related to prognosis of atherosclerotic coronary hemodynamic pathology.